Assessment of Physical Activity of People with Visual Impairments and Individuals who Are Sighted Using the International Physical Activity Questionnaire and Actigraph. (March 2015) - Sadowska, Dorota; Krzepota, Justyna
Introduction: The aim of this study was to analyze the results of walking assessments and total energy expenditure based on a questionnaire and accelerometer measurements among people with visual impairments and those who are sighted. Methods: The study included 25 persons with visual impairments and 25 individuals who are sighted, age 32.3 ± 5.3 years. A weekly measurement of physical activity using the International Physical Activity Questionnaire long form (IPAQ-LF) and accelerometer GTX3 ActiGraph was conducted. Results: It was demonstrated that visual impairment affects walking ability, insofar as it reduces the number of steps taken in a day ( p ≤ .05) (ActiGraph); it does not, however, differentiate physical activity level (IPAQ-LF). Moreover, there has been observed a lower energy expenditure in people with visual impairments in relation to intensive ( p ≤ .01) and moderate-level ( p ≤ .001) physical activity. In the group of people with visual impairments, a correlation ( p ≤ .05) was observed between the energy expenditure associated with walking (IPAQ-LF) and the total weekly energy expenditure associated with physical activity (ActiGraph). Also, a correlation ( p ≤ .05) was observed between the total weekly energy expenditure associated with physical activity in the IPAQ-LF and ActiGraph. Discussion: Regardless of the method used to measure physical activity, on average, participants with visual impairments took a smaller number of steps than participants who were sighted. However, the average number of steps taken by participants with visual impairments was much higher than the 3, 500–5, 000 steps recommended as healthy for a person with disabilities. Implications for practitioners: IPAQ-LF and ActiGraph are effective methods of monitoring physical activity in persons with visual impairments, and may be used in supporting activities that promote taking up physical activity.